Dark Matter Recent Observations and Theoretical Advances - Smith, Michael L. (IntechOpen, 2022)
This book presents several new, important explanations for dark matter, all dissimilar to the discredited subatomic particle-like but invisible matter. One chapter presents evidence that abundant cold hydrogen, baryonic matter, is the source of the missing gravity. Another chapter suggests that dark matter is better explained by stars in spiral galaxies that follow non-Keplerian orbits. A third chapter proposes that gravity attributed to dark matter is due to the sprinkling of black holes throughout galaxies, which is supported by LIGO/Virgo observations. Another chapter questions the assumptions of the Friedmann (FLRW) model, proposing a better method for handling astrophysical data. Additional chapters discuss cosmic ray propagation, axion decay, the cosmological scale factor, and the philosophical outlook of cosmologists when dealing with the questions of dark matter and dark energy.